Effect of Shading Percentage and Potassium Dosages on Growth and Yield of Cutleaf Groundcherry (Physalis angulata L.) - Wiwin Sumiya Dwi Yamika; Nurul Aini; Budi Waluyo; Agus Prayitno Kurniawan (Caraka Tani: Journal of Sustainable Agriculture, 2023)
Cutleaf groundcherry is a medicinal herbaceous plant that has not been widely cultivated. Adjustment to the light intensities supported by the fulfillment of essential macro-nutrient underlies the agronomic consideration for cropping system determination. The study aimed to examine the growth and yield of cutleaf groundcherry grown under shade nets of various shading percentages and potassium application at different dosages. A split-plot design was used for this pot experiment repeated three times. The main plot was the shading percentages (0, 25, 50 and 75), while potassium dosages (0, 60, 120 and 180 kg ha-1) were the subplot. The result showed that several growth variables were affected by the interaction between shading percentages and potassium dosage, whereas yield variables were not. Under the high level of shading, leaf number (41% to 50%), leaf area (28% to 50%), and shoot dry weight (70% to 85%) were reduced at all potassium dosages. Potassium dosage at 120 kg ha-1 was required to achieve better growth under full sun or soft shading. Shading at 50% and upper significantly decreased fruit production by 30% lower fruit number, 50% to 80% lower fruit weight, and 15% lower total soluble solids (TSS). In addition, potassium fertilizer at 120 kg K2O ha-1 improved fruit weight but did not affect TSS. It can be concluded that cutleaf groundcherry is able to grow well under high intensity of light and need an adequate supply of potassium to improve growth, yield and fruit quality.